Interventions to improve adherence to antiretroviral therapy: a systematic review and network meta-analysis. Issue 1 (January 2017) - Kanters, Steve; Park, Jay J H; Chan, Keith; Socias, Maria Eugenia; Ford, Nathan; Forrest, Jamie I; Thorlund, Kristian; Nachega, Jean B; Mills, Edward J
Summary: Background: High adherence to antiretroviral therapy is crucial to the success of HIV treatment. We evaluated comparative effectiveness of adherence interventions with the aim of informing the WHO's global guidance on interventions to increase adherence. Methods: For this systematic review and network meta-analysis, we searched for randomised controlled trials of interventions that aimed to improve adherence to antiretroviral therapy regimens in populations with HIV. We searched Cochrane Central Register of Controlled Trials, Embase, and MEDLINE for reports published up to July 16, 2015, and searched major conference abstracts from Jan 1, 2013, to July 16, 2015. We extracted data from eligible studies for study characteristics, interventions, patients' characteristics at baseline, and outcomes for the study populations of interest. We used network meta-analyses to compare adherence and viral suppression for all study settings (global network) and for studies in low-income and middle-income countries only (LMIC network). Findings: We obtained data from 85 trials with 16 271 participants. Short message service (SMS; text message) interventions were superior to standard of care in improving adherence in both the global network (odds ratio [OR] 1·48, 95% credible interval [CrI] 1·00−2·16) and in the LMIC network (1·49, 1·04−2·09). Multiple interventions showed generally superior adherence to single interventions, indicating additive effects. For viral suppression, only cognitive behavioural therapy (1·46, 1·05−2·12) and supporter interventions (1·28, 1·01−1·71) were superior to standard of care in the global network; none of the interventions improved viral response in the LMIC network. For the global network, the time discrepancy (whether the study outcome was measured during or after intervention was withdrawn) was an effect modifier for both adherence to antiretroviral therapy (coefficient estimate −0·43, 95% CrI −0·75 to −0·11) and viral suppression (−0·48; −0·84 to −0·12), suggesting that the effects of interventions wane over time. Interpretation: Several interventions can improve adherence and viral suppression; generally, their estimated effects were modest and waned over time. Funding: WHO.